ASSESSMENT OF THE MICROBIAL STABILITY OF PRESERVED AND UNPRESERVED BI-HERBAL FORMULATED SYRUP OF CITRUS AURANTIFOLIA WHOLE FRUITS AND GARCINIA KOLA SEED EXTRACTS - Ugwoke, Steven O.; Isah, A. B.; Mahmud, H. S.; Olayinka, B. O.; Igwe, Chibueze James; Kurfi, F. S. (FUDMA JOURNAL OF SCIENCES, 2023)
Liquid herbal products are highly prone to microbial deterioration due to high content of organic matter. The aim of this study was to carry out 90 days microbial stability study of a bi- herbal syrup formulated from extracts of Citrus aurantifolia (CA) whole fruits and Garcinia kola (GK) seeds. The bi-herbal syrup was formulated based on combined extracts minimum bactericidal concentrations (MBC): 8.33mg/mL GA, 30.42mg/mL GK and excipients and compounded by agitation without heat method. Both the preserved and unpreserved samples were challenged with determined population of organisms and counts taken at 7th, 14th and 28th day after inoculation. The zones of growth inhibition (ZGI) and MBC retention of the syrup were determined by Agar well diffusion and Agar–extract–inoculum pour plate methods respectively and the same procedure repeated 60th and 90th days of compounding.There was a slight decline (8.88 %) in the average percentage change of antibacterial activities (ZGI) of the optimum formulation (F3) in a period of 90 days. Only formulation 3 recorded five colonies at the 90 days of compounding. The microbial challenged of the preserved and unpreserved syrup yielded no growth on the 7th, 14th and 28th days, after inoculation. Preservative has no significant contribution to the microbial stability of the formulation, as the unpreserved bi-herbal syrups were much stable within 90 days of stability study and in case of inadvertent introduction of microbes, both preserved and unpreserved syrup would resist microbial growth.